War and warfare since 1945 - Pavelec, Sterling Michael, author.
1 online resource
Keywords: "Beginning with an exploration into the question of what war is, War and Warfare Since 1945 provides a chronological analysis of military history since the end of World War II extending through to an analysis of the limits of modern warfare in the nuclear age with the purpose of examining why war occurs and how it is carried out. The book concludes with an investigation into modern war and speculation on the changing face of warfare."--Provided by publisher.